2022
DOI: 10.3390/ani12182359
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Short-Term and Long-Term Heat Exposures on the Immune Response and Prostaglandin Biosynthesis in Bovine Endometrial Cells

Abstract: Worldwide heat stress (HS) conditions have a negative impact on dairy cow fertility. However, understanding of the effect of heat stress on endometrial functions is still unclear. The present study aimed to investigate the effects of differential heat exposure conditions on the immune response and prostaglandin biosynthesis of bovine endometrium challenged with bacterial lipopolysaccharide (LPS). Cultures of endometrial cells were grown to confluence at 37 °C (control) and 40.4 °C for 24 h after confluence (sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…It has been proposed to be involved in human platelet aggregation as well chemotactic neutrophil migration [ 36 , 37 ]. Furthermore, a study, which investigated the immune response of the cow endometrium to heat stress, reported an increased expression ALOX12 in the group exposed to long-term heat stress [ 38 ]. TRAPPC9 gene is known to play a key role in the NF-κB transcription factor, which involved a number of cellular processes such as innate and adaptive immunity, cellular proliferation, apoptosis, and development [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed to be involved in human platelet aggregation as well chemotactic neutrophil migration [ 36 , 37 ]. Furthermore, a study, which investigated the immune response of the cow endometrium to heat stress, reported an increased expression ALOX12 in the group exposed to long-term heat stress [ 38 ]. TRAPPC9 gene is known to play a key role in the NF-κB transcription factor, which involved a number of cellular processes such as innate and adaptive immunity, cellular proliferation, apoptosis, and development [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, granulosa cells responsible for estradiol production are adversely affected by HS, resulting in decreased estradiol production and subsequent disruption of the estrous cycle in cattle [ 59 , 60 , 61 ]. HS has also been shown to influence corticoid levels, luteinizing hormone (LH), and plasma progesterone in cattle, with alterations in hypothalamus and pituitary gland function leading to changes in the secretion of reproductive hormones [ 9 , 62 , 63 , 64 , 65 , 66 ]. Moreover, HS negatively impacts oocyte quality due to its effects on the hypothalamus and pituitary gland, specifically the LH [ 67 , 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%